If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10j + -14 = 18 Reorder the terms: -14 + 10j = 18 Solving -14 + 10j = 18 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 10j = 18 + 14 Combine like terms: -14 + 14 = 0 0 + 10j = 18 + 14 10j = 18 + 14 Combine like terms: 18 + 14 = 32 10j = 32 Divide each side by '10'. j = 3.2 Simplifying j = 3.2
| g(x-1)=-5x^2+3x | | 78-n=60 | | 10y+1=18 | | 0.15x+0.10(250-x)=29 | | 19x+7y=11 | | g(x-1)=-5x^2+x | | 4(5x-7)=10x+8 | | 7x^2-2x+3=5x^2-10 | | g(x)=-5x^2+x | | 12=21-3h | | 5y-29=x | | 42x-30=360 | | -5.3m+(-3.9m)-17=-19.28 | | 0.6x+3.1=0.5x+1.9 | | 6x+-10x=-4 | | 1/5w-5 | | 6x+-10=-4 | | -2.8c=16.8 | | 18t+13=5t | | 2/14=x/21 | | 9-3F=21 | | 3(x-3)+5=-2(x+3)+5x | | X-0.20=36 | | 5y^2-2x+2=0 | | x*2+6*3=12*3*x | | 18t+13=15t | | 2z=a-bj | | xy=1*3 | | 2.8x+5.6=8.4 | | f(4)=-2x-1 | | x*3x=486 | | (2x+7)(x+5)=0 |